1996
DOI: 10.1016/0014-2921(95)00055-0
|View full text |Cite
|
Sign up to set email alerts
|

Accountability and decentralisation in government: An incomplete contracts model

Abstract: This paper approaches the question of the appropriate level of decentralisation of power in government as a problem in the allocation of control rights under incomplete contracts.The model of the paper compares allocations of power to local, central and regional government as alternative means of motivating governments to act in the interests of citizens. Centralisation allows benefits from policy coordination but has costs in terms of diminished accountability, which can be precisely defined as the reduced pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
339
1
24

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 643 publications
(369 citation statements)
references
References 20 publications
5
339
1
24
Order By: Relevance
“…It also points to the public choice stream of first generation theory and an emerging second theory of fiscal decentralization, which mainly concerns the efficiency trade-off between fiscal centralization and decentralization. Leading studies, that have been classed as parts in the emerging second generation theory, are associated with Weingast (1995), Seabright (1996), Lockwood (2002), Petchey and Levtchenkova (2002), Besley and Coate (2003) and Wagner (2007). The 'second' generation theory of fiscal decentralization has begun to emerge in end of the last decade of the twentieth century, which draws on ideas from outside the public finance literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also points to the public choice stream of first generation theory and an emerging second theory of fiscal decentralization, which mainly concerns the efficiency trade-off between fiscal centralization and decentralization. Leading studies, that have been classed as parts in the emerging second generation theory, are associated with Weingast (1995), Seabright (1996), Lockwood (2002), Petchey and Levtchenkova (2002), Besley and Coate (2003) and Wagner (2007). The 'second' generation theory of fiscal decentralization has begun to emerge in end of the last decade of the twentieth century, which draws on ideas from outside the public finance literature.…”
Section: Resultsmentioning
confidence: 99%
“…The main findings, for the UK and the USA are (i) federalism provides the political basis for the common market; (ii) the prohibitions against the national government's exercise of economic regulation greatly reduced the government's political responsiveness to interest groups; and (iii) the prohibitions on internal trade barriers allowed entrepreneurs, new enterprises, and new economic activities to emerge in new areas that could outcompete interests in older areas (Weingast, 1995). In contrast, Seabright (1996) introduced the notion of 'incomplete contract' to the analysis of fiscal federalism. The author presents elections as incomplete contracts in which some information, in the 'contract', is unverifiable.…”
Section: Petchey and Levtchenkova (2002)mentioning
confidence: 99%
“…15 14 The problem that voters at the national level have a multi-dimensional set of expenditure levels to vote on is an example of a larger problem, namely that accountability for a broader set of policies is difficult to enforce. Seabright (1996) offers one approach to formalizing this difference in accountability at different levels of government. 15 Note that one can have separate subnational and national taxes, as well as transfers.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…In contrast, Seabright [8] constructed a "yardstick competition" model of incomplete contracts under asymmetric information by introducing a local government election factor. He indicated that the voting behaviors of residents ensure the ultimate effort of local governments to provide local public goods if the residents vote after comparing their public goods with those of neighboring jurisdictions.…”
Section: Introductionmentioning
confidence: 99%